RADIKALISME MULTIPERSPEKTIF DALAM KAITANNYA DENGAN STRATEGI PENDIDIKAN KONSELING RELIGIUS - Marsal Yunas , Marsal Yunas; Yuhendara, Depi; Ardimen, Ardimen (Dharmas Education Journal (DE_Journal), 2024)
This research has a very important purpose in understanding and addressing the phenomenon of radicalism. A multidisciplinary approach from the perspectives of psychology, sociology, and theology provides comprehensive insights into the factors influencing the development of radicalism. The research method used is a literature review that focuses on the analysis and synthesis of existing sources such as books, journal articles, research reports, and other sources related to the research topic. Data analysis involves the process of reading, understanding, and synthesizing information from various literary sources.The research results that identify triggers of radicalism from psychological, sociological, and theological perspectives are a crucial initial step. This provides a foundation for the development of more effective prevention strategies. The implementation of religious counseling programs with a holistic approach, including introspection, Tazkiyatun Nafs, Tadabur Qur'an, and Ta'aruf, shows that this research provides concrete solutions to address radicalism. These findings have significant implications for the development of interventions that focus on the root causes of radicalism. By understanding the factors influencing individuals towards radicalism, more accurate and targeted approaches can be developed for the prevention and handling of radicalism cases in society.